Kubrick as Architect - Cherchi Usai, Paolo (Cinémas)

(untitled) (Cinémas, 1998)
ABSTRACTThis essay examines the expressive relevance of architectural elements in the films of Stanley Kubrick. The proposals of Hermann Muthesius and Frank Lloyd Wright concerning the relationships of function to form and of ornement to the architectural whole are considered as a theoretical ground for exploring the ways in which elements such as windows, staircases, corridors and ornament acquire symbolic and narrative functions in Kubrick.